Triple osteotomy of first ray for severe hallux valgus surgery: Long-term follow-up - Borna Guevel; Catherine Rutherfoord; Muhammad Ali Fazal (Acta Orthopaedica et Traumatologica Turcica, 2024)
Objective: This study aimed to present a retrospective case series of the long-term results of severe hallux valgus treated with triple osteotomy of the first ray.